PEMBUKTIAN TERBALIK: SUATU KAJIAN TEORETIS TERHADAP TINDAK PIDANA KORUPSI - Agustinus Samosir (PROGRESIF: Jurnal Hukum, 2017)
The existence of reversing the burden of proof from the perspective of legislation policy is known in the criminal act of corruption as a "premium remediation" provision and also contains a special prevention. The criminal act of corruption as "extra ordinary crimes that require extra ordinary enforcement and extra ordinary measures", then crucial aspects in cases of corruption is the effort to fulfill the burden of proof in the process by law enforcement officers.